The effect of working capital management on firm performance in industrial products sector / Siew Ling Sim and Azlan Ali - Siew, Ling Sim; Ali, Azlan (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
A midst the prevailing corporate ecosystem, it is incontestably that the conspicuousness of firms ought to be placed on their effectiveness in managing short-term resources particularly ensuing the manifestation of the global financial crisis. With the purpose to investigate the effect of working capital management (WCM) on firm performance, this study intends to furnish finance managers as well prospective investors in envisaging the momentous of WCM in trading-off liquidity and returns. This study adopted one-step system generalised method of moments (GMM) in order to capture for the endogeneity issues arising from the unobserved time-invariant firm specific elements as well enhance data efficiency. Adopting a sample of 156 Malaysian public companies listed on Bursa Malaysia in the industrial products sector with the interval of 10 years (i.e. from 2007 through 2016), the study unveils the insignificant linkage between WCM proxy (i.e. CCC) and firm performance (FP). Despite the diminutive and insignificant effect of WCM on FP, the findings still demonstrate a non-linearity appositeness on the existence of optimality of WC requirements and FP. Firm size signified as a substantial control variable that might affect firm profitability as well as firm market valuation due to the competitive edges that could be gained through economies of scale.